Safeguarding the land to secure food in the highlands of Peru: The case of Andean peasant producers - Silvia Sarapura–Escobar; Eric T. Hoddy (Frontiers in Sustainable Food Systems, 2022)
Local or traditional agri-food systems in the Andes depend on community land use planning to maintain the genetic pool of crops and landraces in the face of disease, disasters, and climate change. These systems are managed integrally and on the basis of traditional knowledge around soil conservation, water management and maintaining biodiversity. At the same time, agri-food system research, policy and programming exhibit a limited understanding of local or traditional systems planning and community and cultural contexts. In policy and programming, the treatment of communities as homogenous groups overlooks heterogeneity in local identities, which is reflected for example in different access and use of traditional knowledge among men and women and forms of community organization and customs. The purpose of this article is to respond to this gap by shedding light on the intersecting identities of Andean farmers–peasant women and men–that contribute to the sustainability and resilience of local agri-food systems. Our focus is on intersecting identities and planning processes in particular. We detail the nature and cultural components that make up local agri-food systems in the Andean region and identify policy gaps around identities. To do this, we draw on intersectional feminist thinking, socio-ecological systems and resilience thinking to apply an intersectional lens to the study of planning processes in several Andean communities. Findings identify contributions around soil conservation, biodiversity upkeep, water management, and communal or cultural practices that are shaped by peasant's intersecting identities and their interactions within social-ecological systems. Findings illustrate the importance of multiple social locations, relations, and structures of power, including but not limited to gender, but other categories such as age and ethnicity for the delivery of equitable resilience. We formulate some initial recommendations so that national approaches and interventions better reflect the diversity of Andean people's identities and the way these affect relationships with socio-ecological systems in national and public planning. In particular, we suggest there may be value in exploring further the potential of rights-based approaches for enhancing equitable resilience in Andean agri-food systems. This article should be of interest to academics and practitioners in planning working around local or traditional food systems.